Claiming damages for late delivery of vacant possession: an overview of legal issues and challenges - Amin, Naemah; Kassim, Salina; Sufian, Azlinor (2013)
One of the main duties of the housing developer under the statutory sale and purchase agreement is to complete the construction of the house on time. Schedules G and H of the Housing Development (Control and Licensing) Act 1966 provides that the period of completion and handling over vacant possession for landed property is 24 months and for sub-divided building is 36 months. However in practice, very rare buyers get the keys to their houses on time. According to clause 20(2) of Schedule G, the buyer is entitled to claim for Liquidated Ascertained Damages (LAD) for the delay in completion. It is a statutory remedy to compensate the buyer for the failure of the developer to fulfill his obligation under the agreement to hand over vacant possession on a specific date. The LAD should be calculated from day to day at the rate of 10% per annum of the purchase price. However claiming the LAD is not as simple as it supposed to be since most of the time the developer refuses to pay the LAD for various reasons. Thus a claim for LAD needs to be filed in the court or the Tribunal for Homebuyer Claims. Nonetheless winning the case does not guarantee that the buyer will receive the compensation. Adopting a qualitative method of content analysis, this paper aims to examine various legal issues and challenges faced by consumers in claiming damages for late delivery of vacant possession. The paper also explores possible solutions to existing flaws in the law and practices.